Numerical studies on micro-cracking behavior of transversely isotropic argillaceous siltstone in Longyou Grottoes under three-point bending. (December 2022) - Wang, Song; Zhou, Jian; Zhang, Luqing; Han, Zhenhua; Zhang, Fenxiang; Fu, Yan; Yang, Zhifa
Highlights: Three-point bending models with various bedding planes are created to model the failure behaviors of cavern roofs. Effects of bedding spacings and micro-mechanical properties on transversely isotropic argillaceous siltstone are investigated. Different microcrack propagation patterns during loading are described. Acoustic emission characteristics for bedding planes and rock matrix are revealed. Abstract: Longyou Grottoes, the underground projects with a rich history of thousands of years, are one of the key cultural relics to be protected in China and are actively preparing to apply for a world cultural heritage site. However, due to the shallow buried argillaceous siltstone with low-strength bedding planes, some cavern roofs experienced apparent breakages or large-scale collapses. Clarifying the roof deformation and failure mechanism is essential for the long-term protection of the historical relic and sustainable development of tourism. Productive previous work proved that three-point bending tests of rock samples could reproduce stress states of cavern roofs. Therefore, three-point bending numerical models with various bedding plane structures for Longyou argillaceous siltstone are created in this study to investigate the rock mechanical behaviors. The simulation results show that as bedding mechanical properties decrease, the bending strength (BS) has a slow to fast decrease, indicating that timely protection in Longyou Grottoes before the BS drops sharply is conducive to preventing roof failures. This declining trend is further accelerated when the bedding dip angle changes from horizontal to vertical. Dip angles, mechanical properties, and spacings of bedding planes control fracture modes of models. Moreover, the fitted Gutenberg–Richter-type relationships between acoustic emission (AE) moment magnitudes and logarithmic AE events present high average activity levels and high proportions of large AE events in both bedding planes and rock matrix for models with strong, dispersedly distributed, and near-horizontal bedding planes. In summary, the simulation results reveal the impacts of transverse isotropy in surrounding rocks on roof bending failures, which may provide a valuable reference for the reinforcement and protection of Longyou Grottoes.